2017
DOI: 10.1371/journal.pone.0185129
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the interrelationships among the behavioral tests in rats exposed to chronic unpredictable mild stress

Abstract: The chronic unpredictable mild stress model of depression has been widely used as an experimental tool to investigate human psychopathology. Our objective was to provide an update on the validity and reliability of the chronic unpredictable mild stress model, by analyzing the interrelationships among the indexes using stepwise discriminant analysis and Pearson correlation coefficient to examine the possible combinations. We evaluated the depressive rats in both the presence and the absence of chronic unpredict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 33 publications
4
73
0
5
Order By: Relevance
“…We did not find evidence that over-inhibition increases depression-like behaviors; however, we cannot rule out this possibility. Depression and anxiety are highly comorbid with each other in humans and rodent models (de Graaf et al, 2002;Hu et al, 2017). Furthermore, both anxiety and depression are characterized by reduced activity of the PFC (Martinot et al, 1990;Shin et al, 2001;Phelps et al, 2004;Thompson et al, 2015).…”
Section: Untangling Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find evidence that over-inhibition increases depression-like behaviors; however, we cannot rule out this possibility. Depression and anxiety are highly comorbid with each other in humans and rodent models (de Graaf et al, 2002;Hu et al, 2017). Furthermore, both anxiety and depression are characterized by reduced activity of the PFC (Martinot et al, 1990;Shin et al, 2001;Phelps et al, 2004;Thompson et al, 2015).…”
Section: Untangling Anxiety and Depressionmentioning
confidence: 99%
“…Emotional behaviors are nuanced and multifaceted. For instance, depression can involve despair-related behaviors (measured by tests such as tail suspension and forced swim in rodents), anhedonia (measured by the sucrose preference test), and/or a lack of personal care/grooming (as indicated by the splash test and coat condition) (Hu et al, 2017). More recent behavioral paradigms are also starting to address the cognitive bias towards stimuli with negative valence that can be part of depression (Stuart et al, 2013).…”
Section: Untangling Anxiety and Depressionmentioning
confidence: 99%
“…Depression-like behavior in rats can be reasonably inferred by using appropriate animal models and behavioral tests including the sucrose preference test (SPT), forced swimming test (FST), Y-maze test, and open field test [32]. Among them, the sucrose preference index in the sucrose preference test (SPT) was used to assess the loss of pleasure, the alternating percentage of the Y-maze test was used to assess the brain cognitive function, the forced time of the forced swimming test (FST) was used to evaluate the depression in animal models, and the horizontal and vertical movements in the open field test (OFT) was used to assess the animal evasion [33][34][35]. Our study found that CUMS can reduce the sucrose preference index, horizontal movement, vertical movement activity, and alternating percentage and increase the duration of immobility.…”
mentioning
confidence: 99%
“…The open-field test and elevated plus-maze test are classical methods to assess anxiety-like behavior. Rats suffering from anxiety may display decreased locomotor activity in the open-field test and an inclination to stay in the closed arms of elevated plus-maze test 41 , 42 . Our results showed that rats in the model group developed anxiety-like behavior with higher level of adrenaline in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%